Pengaruh Pendekatan Rme Berbasis Etnomatematika Pada Tari Losuong Khas Kampar Terhadap Kemampuan Pemahaman Konsep Matematis - Putri, Elsi Rahayu; Wahyuni, Molly; Rizky, Lussy Midani (Delta: Jurnal Ilmiah Pendidikan Matematika, 2024)
This research was motivated by the low ability to understand mathematical concepts of class VII students at SMPN 2 Kabun. One solution to overcome this problem is to use an ethnomathematics-based RME approach. The aim of this research is to determine the difference in the ability to understand mathematical concepts of students who apply the ethnomathematics-based RME approach and students who apply conventional learning. This research is an experiment using a quasi experimental design. The research subjects consisted of class VII D, totaling 27 students and VII B, totaling 26 students. The sampling technique used is random sampling. The data collection techniques used were observation sheets and test questions on the ability to understand mathematical concepts. From the results of this research, it can be concluded that there is a difference in the average test results for students' ability to understand mathematical concepts in the experimental class using the ethnomathematics-based RME approach and the control class which applies conventional learning for class VII students at SMPN 2 Kabun. This can be proven through the Independent Sample T-Test, obtaining a sig(2-tailed) value of 0.007 < 0.05, so H0 is rejected and H1 is accepted.